Children in the Principality of Serbia During the Reign of the Defenders of the Constitution – Legislation and Small Images of Reality - Drakić, Gordana; Kulauzov, Maša; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The article treats several provisions of family law regulations introduced during the rule of defenders of the constitution regarding parental law, adoption, foster care and guardianship and their application in practice. The position of children born in and out of wedlock, adopted children and children under guardianship are analysed separately. The authors tend to determine whether there is a gap between the letter of the law and reality. The answer to that question is positive. Concerning marital children, such practice was due to the behaviour of their parents. However, authorities bear the responsibility for misapplication of laws in respect of non-marital children and children under guardianship. The exact extent of divergence between regulations and reality is yet to be determined.